PENGARUH SIKAP DAN PERSEPSI TERHADAP NIAT KOMPLAIN PELANGGAN PADA MASKAPAI PENERBANGAN DI BANDAR UDARA INTERNASIONAL ADI SUTJIPTO - Wawan Riyanta (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Airlines need to know the attitudes and perceptions of passengers in complaining the airline services so that they do not cause losses. Attitudes and perceptions described in several aspects that affect the intention of customer complaints, so that the influence between these aspects will be known. The design of this study uses a causal research design, because it needs to see one or more variables cause or be a determinant of other variables. Data use Smart PLS with the help of Smart PLS 2.0 M3 software. The results of the study show that attitude towards complaints behavior affects the intention to complain to airlines, the attitude towards complaints behavior is influenced by Consumer Avoidance, Complaint Experience and ability to control. Perception of the value of complaints affects the intention to complain, the perception of the value of complaints is influenced by Consumer Avoidance, Complaint Experience and ability to control. Perceptions of the likelihood of successful complaints affect the intention to complain, Perceptions of the likelihood of successful complaints are influenced by the ability to control, while the Customer Avoidance and Complaints Experience factors do not affect perceptions of the perception of the likelihood of successful intentions of complaints on airlines.